Lietuvos Didžiosios Kunigaikštystės paveldo reikšmės populiariosiose tautinio naratyvo interpretacijose - Šutinienė, Irena (Lietuvos istorijos studijos, 2008)
The article presents the data of empirical research (namely, a representative survey of Lithuanian adult population as well as focused interviews) of popularity and uses of symbolic representations of the period of the Great Duchy of Lithuania. About a third part of inhabitants sets a great store on the heritage of the Great Duchy of Lithuania as significant for their national identity. The myths supporting the continuity of national identity (the founding, "descent" myths) grow in popularity, while the significance of the myths serving mobilization for collective action (that of the "golden age" and others) is on the decrease. The significance of the interpretations of symbols and myths supporting civic-territorial dimensions of Lithuanian national identity increases as well: it is expressed in importance for contemporary identity of the values of tolerance, civic national identity, multiculturalism that are highlighted in popular interpretations. There are tendencies supporting social integration of ethnic groups, namely Polish and Lithuanian, in popular interpretations of the heritage of the Great Duchy of Lithuania: there are tendencies of "hybridization" in popularity and interpretations of some symbolic elements of that heritage among Poles and Lithuanians, and the importance of conflict interpretations of some symbols diminishes, especially in the interpretations of the younger generations.